A systematic review of qualitative studies of adults' experiences of being assessed for psychological therapies. (8th January 2019) - Sweeney, Angela; Clement, Sarah; Gribble, Kate; Jackson, Elizabeth; Carr, Sarah; Catty, Jocelyn; Gillard, Steve
Abstract: Objective: To synthesize the qualitative literature on adults' experiences of psychological therapy assessments. The review was led by people with experience of undergoing assessments, with high levels of client involvement throughout. Search strategy: A comprehensive search of electronic databases was undertaken, with additional search strategies employed to locate further literature. Inclusion criteria: Studies were included that qualitatively explored the experiences of people aged 16+ who had been assessed for psychological therapy services. Assessments could be structured or unstructured. Qualitative was defined as any analysed account of people's experiences, including qualitative survey data. Data extraction and synthesis: Literature quality was appraised using the Critical Appraisal Skills Program checklist, modified to include client involvement and intersectionalities. Following data extraction, thematic synthesis was used to synthesize findings across studies. Results: Of 12 743 titles were screened, with 13 studies relevant to the review. Themes and subthemes were identified at three stages of the assessment process: the journey to the assessment, at the assessment, and after the assessment. Findings highlighted the emotional impact of assessments, collaboration, intersectionalities, rights, pathologization, socioeconomic restrictions, and information and support needs. Implications and limitations were indicated. Discussion and conclusions: Findings were situated within the trauma‐informed (TIA) literature. Trauma‐informed assessment principles, including collaborative assessments, may be fruitful means of improving people's experiences. Whilst the benefits of collaboration appear self‐evident, explicitly collaborative approaches were not the norm, nor were studies conducted independently. Further service user research is needed. A greater understanding of the experience of minority groups is also needed.